Medical management ofeEctopic gestation following a failed bilateral tubal ligation. (2020)
The objective of this paper is to emphasize that ectopic pregnancy can occasionally occur after a previous bilateral tubal ligation. Affected women may be reluctant to undergo a repeat surgery and medical management is an acceptable approach in suitable cases. The case was a 40-Year-old G5P4+0 (3A) woman who presented to gynaecology clinic with 7-weeks history of amenorrhoea and 1 day history of bleeding from the vagina. She has had two previous caesarean section and bilateral tubal ligation during her last confinement in 2018. Ectopic pregnancy was confirmed, and she was medically managed with methotrexate. Pregnancy after bilateral tubal ligation is rare and when it occurs are rarely ectopic pregnancy. Medical management can be offered to suitable patients where there is facility for follow-up.